PENYELESAIAN KREDIT MACET DENGAN JAMINAN FIDUSIA AKIBAT DEBITUR WANPRESTASI - Inten Purnama Sari, I Gusti Ayu; Artadi, I Ketut (Kertha Semaya : Journal Ilmu Hukum, 2014)
One of banking service to give credit to their customers. Credit given by bank hasrisk, so that is implementation within the bank should pay attention to the principles ofprudent credit. One of the binding guarantee that the fiduciary. At the time the debtor nonfullfill,ment of a liability that has been agreed, then they will be a proof that the debtordefaults. Fiduciary guarantee regulated in Indonesian Law Number 42 of 1999 aboutFidusia Guarantee. The stuck of credit settlement with fidusia guarantee conducted by bankis by doing underhanded sale on mutual agrrement between debtor and creditor party inorder to obtain higher sale price. The problems faced by back in settling stuck creditespecially with fidusia guarantee consist of judicial and non judicial problems. The judicialproblem in settlement process of this stuck credit relates to no availability of preferencerights on banks as the credit issuer so the bank statusbecomes weak, in the meanwhile thenon judicial problem is hand over of object to other person without bank knowledge.
Keywords: stuck credit, fidusia guarantee, debtor, wanprestasi